Establishing and changing meaning by means of classical conditioning using the paired-associate method - Doyo, Ma. Ceres P. ([Metro Manila] Psychological Association of the Philippines, 1971)
The purpose of this study was to finsd whether the different factors of meaning namely, evaluate, potency and activity, can be conditioned to nonsense syllables and also whether these meanings which have been acquired can be changed. Results showed that meaning can be acquired and changed; however it was observed that individual meaning factors cannot be purely conditioned to nonsense sylabbles.
Includes bibliographical references (page 124)
Keywords: Psychology Philippines -- Periodicals